THE IMPLEMENTATION OF THE PROBLEM-BASED LEARNING (PBL) MODEL USING A VIRTUAL LAB TO IMPROVE STUDENTS' LEARNING OUTCOMES ON POTENTIAL AND KINETIC ENERGY MATERIAL - Khoiroh, Nisaul (Journal of Higher Education and Academic Advancement, 2025)
Objective:  This study aims to evaluate the effectiveness of implementing the Problem Based Learning (PBL) model in improving students' learning outcomes on the topic of potential and kinetic energy in Class X at SMK Putra Perdana Indonesia. Method: The research was conducted through two learning cycles using an innovative PBL approach integrated with virtual lab activities. Data were collected through pretests and posttests, observations, and analysis of student presentations. Results: The results showed an increase in the average score from 50.3 (pretest) to 70 (posttest), indicating percentage of 28.57% improvement in student learning outcomes. In addition, students' motivation and participation also increased during the learning process. Challenges such as time management and uneven student understanding were successfully addressed through thorough planning, individual guidance, and the use of heterogeneous group systems. Novelty: Therefore, it can be concluded that PBL is effective in enhancing students' conceptual understanding of physics and their critical thinking skills.